If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(-3) = 9 + -4 Reorder the terms for easier multiplication: -3f = 9 + -4 Combine like terms: 9 + -4 = 5 -3f = 5 Solving -3f = 5 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by '-3'. f = -1.666666667 Simplifying f = -1.666666667
| t^2+11+24=0 | | 2(r-7)-(r-8)=3 | | 7+25=18+x | | X-3+2x=x+5 | | 7(4x-2)=5(2-x) | | x+25+x+-5=90 | | (2.4)(2.0)=(X)(0.5) | | 2(3.14)14= | | -(x+8)=-9x+56 | | (2c+5)(c+4)=0 | | 7+3y=18+x | | 3e-x-1=5 | | -16x^2+80= | | log(y)=1.9747log(x) | | 69x+9y=900 | | y=x^2+49 | | 6z-12z=1-18 | | 11n+9=6n+44 | | (9*4)-5=9*(4-5) | | -6h+4=-10h+16 | | 10p(4/5p) | | 5x+10-3x-3= | | y=4x^2+12x-5 | | -8x-18=-146 | | 4t-2=6t+6 | | -16x^2+80x= | | -5x*2x= | | x=1.8*x+32 | | 2x+14=-6x+34 | | a(n)=12+(n-1)(3) | | -6h+4=-10h+6 | | log(6x+12)=1+log(x-6) |